Analisis Gaya Bahasa Pada Lirik Lagu 《伟大的渺小》 (Wěidà de miǎoxiǎo) Karya 林俊杰 (JJ Lin) - Bella Fitriandini; Ressi Maulidina Delijar (Asosiasi Program Studi Mandarin Indonesia, 2022)
In making literary, it is often found there is a style of language in every writing. Not only found in poetry or stories, but language style is also often found in song lyrics. By paying attention to the use of language style in song lyrics, this study discusses the analysis of language style in a mandarin song entitled 伟大的渺小》(Wěidà de miǎoxiǎo/Little Big Us) by 林俊杰 (Línjùnjié/JJ Lin). The purpose of this study are (1) describe the types of language style used in JJ Lin's song lyrics (2) describe the relationship between language style and the meaning contained in JJ Lin's song lyrics. By using qualitative methods and a stylistic approach, this study can describe the types of language styles and meanings contained in the lyrics of the song. The results of this study indicate that the use of hyperbole is the most dominant type of language style in JJ Lin's song lyrics and it is found the message the songwriter wants to convey to his listeners.Keywords: Language style; song lyrics; meaning